Role of acid solvent to prepare highly active PtSn/theta-Al2O3 catalysts in dehydrogenation of propane to propylene - Prakash, Natarajan; Lee, Mi-Hyun; Yoon, Sungho; Jung, Kwang-Deog (ELSEVIER, 2017)
The PtSn bimetallic catalysts with a high Pt metal dispersion were successfully prepared using acid solvent. The aqueous mixed acid solution of HCl and HNO3 was used as solvent to dissolve the Pt and Sn precursors. The (Pt-Sn)A, (Sn-Pt)A and (PtSn)A catalysts (PtSnA catalysts) were prepared by sequential impregnation of Pt and Sn, sequential impregnation of Sn and Pt and co-impregnation, respectively. The metal dispersions of the (Pt-Sn)A, (Sn-Pt)A and (PtSn)A catalysts were 21.6%, 25.9%, 24.4%, respectively. For comparison, the (Pt-Sn)E, (Sn-Pt)E and (PtSn)E catalysts were prepared using ethanol similarly to the PtSnA catalysts. The metal dispersions of (Pt-Sn)E, (Sn-Pt)E and (PtSn)E catalysts (PtSnE catalysts) were 7.1%, 5.4%, and 7.5%, respectively. The metal dispersions of the PtSnA catalysts were three times higher than those of the PtSnE catalysts. The Pt metal particle sizes of the PtSnA catalysts were measured to be 4.4-6.9 nm by chemisorption and 1.9-2.3 nm by Technai STEM images. However, it was observed by a Titan STEM that the aggregates of the metal sub-nanoparticles were dispersed on the PtSnA catalysts. All the metal particles on the PtSnA catalysts existed in the sub-nano sizes. The particle size of 1.9-2.3 nm by the Technai STEM is the size of the aggregates of the metal sub-nanoparticles. Propane dehydrogenation was conducted with the prepared catalysts at 873 K and a GHSV of 22,500 mLg(cat)(-1) h(-1). The initial catalytic activity decreased in the order of (Sn-Pt)A > (PtSn)A > (Pt-Sn)A > (PtSn)E >> (Pt-Sn)E > (Sn-Pt)E. The PtSnA catalysts showed not only the high activity but also the high selectivity and stability in propane dehydrogenation for 15 h. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: PT-SN CATALYSTS; N-BUTANE DEHYDROGENATION; ISOBUTANE DEHYDROGENATION; RENEWABLE RESOURCES; TIN; PLATINUM; PERFORMANCE; PT/AL2O3; BEHAVIOR; OLEFIN